2005 IEEE International Symposium on Circuits and Systems
DOI: 10.1109/iscas.2005.1464755
|View full text |Cite
|
Sign up to set email alerts
|

On the Effect of Time Delays in Negative Feedback Amplifiers

Abstract: Abstract-Time delays are intrinsic to all existing devices and circuits. For the majority of applications, time delays are so small that their effects can be disregarded. However, when considering feedback amplifiers, depending on open-loop poles and loop gain, the effect of a small time delay inside the feedback path may turn to be of considerable importance. This paper analyzes the frequency response effects associated with time delays in feedback amplifiers, exploiting these effects to achieve bandwidth enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…It was also observed that for the 2 nd order approximation, the bandwidth gain reduction was more pronounced. This agrees with the bandwidth gain reduction effect observed in second order delayed feedback systems, as reported previously in [1,2].…”
Section: Simulation Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…It was also observed that for the 2 nd order approximation, the bandwidth gain reduction was more pronounced. This agrees with the bandwidth gain reduction effect observed in second order delayed feedback systems, as reported previously in [1,2].…”
Section: Simulation Resultssupporting
confidence: 92%
“…The best scenario is a frequency response exhibiting peaking behaviors near the cut-off frequency region. However, depending on the amount of the delay, it is also possible to violate the stability restrictions [1]. On the first two scenarios it is possible to optimize bandwidth adding a delay element in the loop.…”
Section: Delay Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Only recently has Nowack [2] rediscovered the problem of a delay-induced instability phenomenon in highgain high-bandwidth transimpedance amplifiers. Nevertheless, the usage of small delays inside the feedback path of feedback amplifiers as a means of achieving larger GBW was not ever covered [6,7]. Figure 1(b) shows an NDFA comprising a delay element inside the feedback loop (having a delay value of seconds).…”
mentioning
confidence: 99%